1978
DOI: 10.1126/science.199.4324.75
|View full text |Cite
|
Sign up to set email alerts
|

Pierce's Disease of Grapevines: Isolation of the Causal Bacterium

Abstract: A Gram-negative, rod-shaped bacterium has been consistently isolated from grapevines with Pierce's disease. Grapevines inoculated with the bacterium developed Pierce's disease, and the bacterium was reisolated from the plants. The bacterium was serologically and ultrastructurallv indistinguishable from the one in naturally infected plants, and also indistinguishable from a bacterium isolated from almonds with almond leaf scorch disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
0
18

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(120 citation statements)
references
References 7 publications
0
98
0
18
Order By: Relevance
“…Only in the mid-1970s, after it was shown that 'yellows' diseases of plants were of bacterial origin (phytoplasmas and spiroplasmas; Doi et al 1967), were diseases caused by X. fastidiosa determined to also have bacterial etiology (Hopkins and Mollenhauer 1973). That breakthrough led to its axenic culture in 1978 (Davis et al 1978); and the bacterium was named X. fastidiosa one decade later (Wells et al 1987). Despite its importance, research on this pathogen remained limited until a new disease in citrus emerged in Brazil in 1987 and another reemerged in California in the late 1990s (Hopkins and Purcell 2002).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Only in the mid-1970s, after it was shown that 'yellows' diseases of plants were of bacterial origin (phytoplasmas and spiroplasmas; Doi et al 1967), were diseases caused by X. fastidiosa determined to also have bacterial etiology (Hopkins and Mollenhauer 1973). That breakthrough led to its axenic culture in 1978 (Davis et al 1978); and the bacterium was named X. fastidiosa one decade later (Wells et al 1987). Despite its importance, research on this pathogen remained limited until a new disease in citrus emerged in Brazil in 1987 and another reemerged in California in the late 1990s (Hopkins and Purcell 2002).…”
Section: Historymentioning
confidence: 99%
“…Since it was first cultured in the laboratory, attempts to deliver X. fastidiosa cells to vectors from growth media have been unsuccessful (Davis et al 1978), until it was discovered that plant structural polysaccharides result in phenotypic changes in X. fastidiosa, inducing its transmissibility by leafhoppers (Killiny and Almeida 2009b). Plant polysaccharides induce phenotypic changes leading to higher degrees of adhesiveness and, consequently, attachment to vectors after acquisition from plants (Killiny and Almeida 2009b).…”
Section: Vector Colonizationmentioning
confidence: 99%
“…The disease actually is caused by a strain of the bacterium Xylella fastidiosa (Davis et al 1978). Strains of this bacterium also inflict damage on many other plant species, including almond, citrus, elm, maple, oak, oleander, stone fruit and sycamore.…”
Section: Cooperative Efforts Contained Spread Of Pierce's Disease Andmentioning
confidence: 99%
“…This bacterium infects the xylem vessels of plants and causes significant economic losses in several crops (Hopkins 1989), such as the leaf scald in plums (Raju et al 1982), phony peach disease (Wells et al 1987), pierce's disease of grapevine (Davis et al 1978), leaf scorch in coffee (Hartung et al 1994) and citrus variegated chlorosis (CVC) (Chang et al 1993, Hartung et al 1994, among others. Among the symptoms, X. fastidiosa causes the death of susceptible plants.…”
Section: Introductionmentioning
confidence: 99%